Exposure pattern of house dust mites in childhood asthma along the year: A series of 10 cases - Zakiudin Munasir; Lenny S. Budi; Titi Sularyo; Sri Rezeki Hadinegoro (Indonesian Pediatric Society, 1999)
House dust mite (HDM) is one of the inhalant allergens causinginflammation of respiratory tract. More than 100 dust mites/ gram house dust may cause sensitization in childhood asthma, while more than >500 house dust mite/gram house dust may cause asthma attack. This report aimed to determine the exposure pattern of house dust mites on 10 asthmatic children during one year. Homevisit to all patients was done every month to obtain house dust sample, measurement of relative humidity, bed room temperature, and to evaluate the clinical scores and peak expiratory flow rate (PEFR). The range value of house dust mite/gram house dust was 0-340. This study shows that house dust mite may cause of acute asthma attack when accompanied by nonspesific stimuli. In September the relative humidity is high, the temperature is low, and the amount of house dust mite/gram of house dust is highest, in contrast to in August and December. This study shows no seasonalvariation. The amount of house dust mite/ gram of house dust was found higher at the mattress than in the floor of bed room. The species of house dust mite that predominantly found is Dermato- phagoides pteronyssinus. We conclude that house dust mite may cause acute asthma attack whenever accompanied by nonspesific stimulus.